THE EFFECT OF PEBALAV (PERINEAL BATH AND LAVENDER OIL) ON THE INTENSITY OF PERINEAL WOUND PAIN IN POSTPARTUM MOTHERS IN THE NGAWEN COMMUNITY HEALTH CENTER, BLORA REGENCY - Ardhita Listya Fitriani; Putri Rahma Dini; Siti Fatimah; Hera Karomah (Jurnal Smart Kebidanan, 2026)
ABSTRACT   Background: Perineal wound pain is a common problem in postpartum women caused by stitches due to perineal tears. Perineal stitches are experienced by 85% of women who give birth vaginally. Perineal wound pain can interfere with comfort and the healing process of perineal wounds. PEBALAV (Perineal Bath and Lavender Oil)  is a non-pharmacological therapy that can reduce pain through a relaxing effect and by increasing blood circulation as well as cleaning and caring for perineal wounds. Purpose: to determine the effect of PEBALAV (Perineal Bath and Lavender Oil) in reducing perineal pain in postpartum mothers in the Ngawen Community Health Center area. Method: Quasi-experimental study with a one-group pretest-posttest design. The population consisted of 60 postpartum women who delivered in the Ngawen Community Health Center area during March–April 2026. The sample consisted of 30 postpartum mothers in the Ngawen Community Health Center area, Blora Regency. The research instrument used was the Numeric Rating Scale (NRS) for pain assessment. Data analysis used the Wilcoxon test. Results: The average perineal pain score was 4.3, or moderate, before the PEBALAV (Perineal Bath and Lavender Oil) intervention, and the average perineal pain score was 2.13 after the intervention. Postpartum women experienced an average pain reduction of 2.17 after receiving the PEBALAV (Perineal Bath and Lavender Oil) intervention. There was an effect of PEBALAV (Water and Lavender Oil Soak) on reducing perineal pain in postpartum women at the Ngawen Community Health Center (PHC) with a p-value of 0.000 <0.05. Conclusion: PEBALAV (Perineal Bath and Lavender Oil)) therapy has an effect on reducing perineal pain in postpartum women.